Representasi Kesehatan Mental Dalam Film “Kukira Kau Rumah” Sebagai Media Komunikasi Visual (Analisis Semiotika Charles Sanders Peirce) - Kusuma, Luken; Utomo, Ichsan Widi; Irhamdhika, Gema (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The film "Kukira Kau Rumah" is the directorial debut of Umay Shahab that was first screened in Jogja-NETPAC Asian Film Festival in 2021, before finally officially released in Indonesian theaters on February 3, 2022. This film has a duration of 30 minutes. specifically bipolar disorder, through a main character named Niskala who struggles dealing with social stigma and limited support from the surrounding environment. To analyze this film, this study used a descriptive design with a qualitative approach as the primary method chosen by the researcher. The results of the study show that In the movie Kukira Kau Rumah, there are representations of two mental disorders namely bipolar disorder and depressive symptoms. Bipolar disorder is shown through Niskala’s extreme and unstable behavior such as when she appears very energetic, speaks fast and acts impulsively without considering the consequences. Meanwhile, symptoms of depression are shown through scenes when Niskala is alone, crying, losing interest in the surroundings, as well as showing a blank expression and emotional exhaustion. Both conditions are contrastively described to show the unbalanced mood dynamics, which are characteristic of bipolar disorder sufferers, while showing a profound emotional impact on their daily lives.